Final answer:
The distance from point A to A' after translation is 2 sqrt(13).
Step-by-step explanation:
The given points are A(-6,-5) and A' is obtained by translating A using the transformation T: (x,y) -> (x + 4, y + 6).
So the coordinates of A' are (-6 + 4, -5 + 6) which is (-2,1).
To find the distance from A to A', we can use the distance formula.
Distance = sqrt((x2 - x1)^2 + (y2 - y1)^2)
Substituting the coordinates of A and A' into the formula, we get Distance = sqrt((-2 - (-6))^2 + (1 - (-5))^2).
Calculating the distance, we get Distance = sqrt((4)^2 + (6)^2) = sqrt(16 + 36) = sqrt(52) = 2 sqrt(13).